A New Data Coding Algorithm for Secure Communication of Image - Hidayet Oğraş (Chaos Theory and Applications)
This paper proposes a new entropy-sensitive based data coding algorithm for the secure communication of image information between transceiver systems. The proposed algorithm utilizes chaos theory and the image information content of the reference image to create sensitivity on the decoding side for a high level of secrecy. It successfully recovers secret images at the receiver’s side using secret code series derived from both the secret and reference images, instead of direct transmission of secret image. The image information can be retrieved only through the same reference image, the same system parameters and identical code series using the proper decoding technique at the receiver. Quantitative results indicate that the average coding time for 128x128 images is approximately 0.27 seconds, while the extraction time averages 0.19 seconds, yielding impressive rates of 0.487 Mbps and 0.677 Mbps, respectively. Moreover, according to qualitative results, even a single-bit change in the reference image leads to a complete inability to decode the secret image, highlighting the robustness and security of the algorithm. Experimental results on various images show that the proposed algorithm is reliable, fast and effective in securing confidential image information.